A saúde do povo Kaingang da aldeia Três Soitas, município de Santa Maria, RS, e sua relação com os usos do território - Aguiar, Priscila de (2023)
The reality of indigenous health is complex, a fact that requires a multidimensional analysis resulting from the breadth of disputes over land ownership, use and exploitation, and other natural and / or human resources, which bring interference to the debate on a global, national, regional and local scale, interrelating and directly impacting the local construction of the indigenous health network. The legislation ensures that indigenous groups will not be removed from their lands, except in events which exposes them to risks, such as catastrophe or epidemic, or in the interest of the country's sovereignty, after deliberation by the National Congress. Brazilian law provides for the conditions for the provision of health care to indigenous peoples within the scope of the Unified Health System under the responsibility of the Ministry of Health, and defines that attention to indigenous health is the duty of the Government and will be provided in accordance with the Federal Constitution of 1988, aiming at the universality, comprehensiveness and equanimity of health services. Objective: Analyze the Indigenous Health Care Policy and the territorialization process of this policy in Brazil. Method: It is a qualitative. The setting for this research will be the municipality of Santa Maria, located in the central region of the State of Rio Grande do Sul. The research used secondary and primary data sources, with the technique of systematic observation and research opinion application. The findings indicate that there is no guarantee of the right to education, water security, food security, health, and life for indigenous peoples without the assurance of the right to territory and their unique usufruct, from their ways of be and being. As the Indigenous social movement progresses in the reclaiming of territories, Indigenous rights are becoming more tangible and accessible. It is expected to contribute to the improvement of public health policies of Santa Maria for indigenous peoples.